THE PROHIBITION OF ABSENTEE OWNERSHIP OF AGRICULTURAL LAND AND THE LEGAL LIABILITY OF THE NATIONAL LAND AGENCY: LARANGAN KEPEMILIKAN TANAH PERTANIAN DAN TANGGUNG JAWAB HUKUM BADAN PERTANIAN NASIONAL - Shintyana Dewi; Soediro; Amjad Majdi bin Muhamad Amin (Universitas Majalengka, 2024)
Absentee ownership of agricultural land is a situation where agricultural landowners are not directly involved in the agricultural activities carried out on their land. This often occurs when the landowner lives outside the farming area. The provision of absentee ownership of agricultural land can affect farmland management, and agricultural productivity. This abstract aims to evaluate the legal aspects of absentee ownership of agricultural land by considering several factors. First, we analyze the application of Government Regulation Number 41 of 1964 in Plaosan Village regarding absentee land. Several studies have shown that the absence of a landowner can hinder growth and innovation in the agricultural sector. However, the factor depends on the skill level of the farmer. Furthermore, we analyze the legal liability of the National Land Agency (BPN) in resolving absentee land ownership issues. The existence of landowners who are not involved in agricultural activities can lead to legal uncertainty, low agricultural productivity, and difficulties for interested parties in obtaining benefits from the land. In this context, the role of the National Land Agency (BPN) as a government agency responsible for land management and registration becomes very important. This research uses a normative legal research method by conducting a literature study of laws and regulations related to absentee ownership of agricultural land. The results of this research are expected to provide a basis for better policies in managing agricultural land ownership involving absentee owners, so as to increase productivity, efficiency, and welfare for all parties involved in the agricultural sector.